Netter's Neurology - Srinivasan, J. Jayashri; Scott, B. Brian; Chaves, C. J. Claudia J.; Small, J. E. Juan E.; Netter, F. H. Frank H. (Elsevier, 2020)
Perfect for residents, medical students, generalists, nurses, and other healthcare professionals who need a practical, working knowledge of neurology, Netters Neurology, 3rd Edition, provides a concise overview highlighted by unique, memorable Netter illustrations. This award-winning visual resource showcases the well-known work of Frank H. Netter, MD, and his successor, Carlos Machado, MD, a physician who has created clear, full-color illustrations in the Netter tradition.